Student behavioural intentions to use eLearning system in Indonesian higher education during the COVID-19 pandemic: A structural equation model - Sondakh, Jullie; Asaloei, Sandra; Werang, Basilius (Journal of University Teaching and Learning Practice, 2023)
The rapid transformation in information and communication technology (ICT) has influenced change in other areas of human lives, including in the teaching and learning process in higher education institutions. This study explores: a) how student perceived usefulness, perceived ease of use, attitude toward use, and behavioural intention to use an eLearning system (using the Technology Acceptance Model (TAM)); and b) validity testing of the underlying causal relationships between perceived usefulness, perceived ease of use, attitude towards use, and behavioural intention to use in the eLearning system context. To do so, a quantitative survey was used with 255 student participants, drawn conveniently from a local population of 745 accounting students studying at Sam Ratulangi University, Indonesia. The result of descriptive statistical analysis using the SPSS showed that all the items of perceived usefulness, perceived ease of use, attitude towards use, and behavioural intention to use were highly perceived by the accounting students of Sam Ratulangi University. The result of confirmatory factor analysis using structural equation modelling in IBM’s AMOS software showed that all the constructs developed in this study are feasible to examine the relationships between perceived usefulness, perceived ease of use, attitude towards use, and behavioural intention to use in the eLearning system context. The findings have important implications for the successful implementation of online teaching and learning in higher education institutions. The findings could be critical for college and university leaders to investigate the merit of eLearning systems in terms of their utility in increasing students’ intention to use eLearning systems in their learning journeys.